87.3k views
4 votes
W^3 x w^-5
please help and please explain

User Erdi ?Zgi
by
4.5k points

2 Answers

3 votes
= W^3+(-5)
= W^3-5
= W^-2
User MadNeox
by
5.6k points
5 votes

Answer:


\Large \text{$ (1)/(w^2) $}

Explanation:

Given the exponential expression,
\displaytext\mathsf{w^3\:*\:w^(-5)}, where it involves the multiplication of the same base, w, with varying powers.

Using the Product Rule of Exponents, where it states that,
\displaystyle\mathsf{a^(m)\:*\:a^(n)\:=\:a^((m\:+\:n))}.

Hence, we simply need to add the exponents:


\displaytext\mathsf{w^3\:*\:w^(-5)\:=\:w\:^([3\:+\:(-5)])\:=\:w^(-2)}

Next, apply the Negative Exponent Rule, where it states that:
\displaystyle\mathsf{a^(-n)\:=\:(1)/(a^n)}.

Transforming the negative exponent of
\displaytext\mathsf{w^(-2)} becomes a positive exponent by using the Negative Exponent Rule.


\displaytext\mathsf{w^(-2)\:=\:(1)/(w^2)}

User Steven Aguilar
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.